Towards better diagnostic tools for liver injury in low-income and middle-income countries - Saundria Moed; Muhammad H Zaman (BMJ Global Health, 2019)
Liver disease is a significant public health burden in both high-income and low-income countries, accounting for over 2 million annual, global deaths. Despite the significant mortality burden, liver diseases are historically a neglected problem due to a lack of accurate incidence and prevalence statistics, as well as national and international programmes targeting these diseases. A large portion of deaths due to liver diseases can be treated (eg, chronic hepatitis B), cured (eg, chronic hepatitis C) or prevented (eg, acute liver failure due to medications) if prompt diagnosis is made, but currently diagnostic methods fall short. Therefore, there is a critical need to fund the development of prompt, effective diagnostics for liver function, specifically in low-income and middle-income countries where the landscape for this testing is sparse. Here, we review and compare available and currently emerging diagnostic methods for liver injury in low-income and middle-income settings, while highlighting the opportunities and challenges that exist in the field.